Asking for Young Offenders: What is the Fate of Restorative Justice within Nigeria's Discretionary Diversion Policy? - Okoh, Collins (Strathmore Law Review, 2021)
The young offenders’ justice system in Nigeria represents an area where the law has failed to respond properly to the needs it was designed for. Many empirical studies conducted over 17 years show that young offenders in Nigeria are continuously subjected to the state-sanctioned processes and practices—the formal justice system—which goes against the best interest of the child principle. This is despite the fact that Nigeria has ratified the United Nations Convention on the Rights of the Child and domesticated it through the Child’s Rights Act 2003 (CRA). The problem is that the diversion policy framework under the CRA offers discretionary powers to state officials who drive the formal justice system. This allows these officials to choose whether to divert cases and to select which restorative justice mechanisms to divert to at any level of the young offenders’ justice system. This paper argues that taking away such discretionary powers can help to improve the treatment of young offenders under the Nigerian criminal justice system. Drawing lessons from New Zealand, this paper suggests, among others, a mandatory diversion policy for a committed practice of juvenile restorative justice in Nigeria.